Experimental study on dynamic response of existing tunnel lining structure by adjacent tunnel blasting load - Bin Zhang; Chen Li; Jianlin Li; Ruizhe He; Xuefu Zhang; Xiaogang Li; Zijian Wang; Yi Wu (Scientific Reports)
Abstract During tunnel construction by the drilling and blasting method, the blasting stress waves may affect the mechanical response of existing tunnel lining structure. Based on the similarity theory, a mechanical response of existing tunnel lining structure by blasting model test is designed. The similar material of surrounding rock, explosives, and tunnel lining structure are determined by the similarity of physical mechanical parameters. This study investigates the mechanical response of existing tunnel lining concrete and reinforcing steel‌ by the action of adjacent tunnel blasting. The experimental results reveal the maximum strain distribution and stress peak value of existing tunnel lining concrete and reinforcing steel‌ affected by blasting load. Meanwhile, the equations are established between the peak particle velocity (PPV) and the strain (or stress) in tunnel lining concrete and reinforcing steel‌ affected by adjacent tunnel blasting as well. These Eqs. (13) and (14) can be used to predict the maximum stress value of existing tunnel lining concrete and reinforcing steel‌ by the action of blasting load. Simultaneously, these equations have been validated and adjusted by an actual engineering project field test. Thus, evaluating the stress states of tunnel lining caused by adjacent tunnel blasting is more effective. This finding is of great significance for evaluating the stress state of existing tunnel lining structure, as well as providing theoretical guidance and reference for the design of blasting parameters on adjacent tunnel construction.